Immunodiagnosis of Canine Visceral Leishmaniasis Using Mimotope Peptides Selected from Phage Displayed Combinatorial Libraries. (29th January 2015) - Toledo-Machado, Christina Monerat; Machado de Avila, Ricardo Andrez; NGuyen, Christophe; Granier, Claude; Bueno, Lilian Lacerda; Carneiro, Claudia Martins; Menezes-Souza, Daniel; Carneiro, Rubens Antonio; Chávez-Olórtegui, Carlos; Fujiwara, Ricardo Toshio
Abstract : ELISA and RIFI are currently used for serodiagnosis of canine visceral leishmaniasis (CVL). The accuracy of these tests is controversial in endemic areas where canine infections by Trypanosoma cruzi may occur. We evaluated the usefulness of synthetic peptides that were selected through phage display technique in the serodiagnosis of CVL. Peptides were chosen based on their ability to bind to IgGs purified from infected dogs pooled sera. We selected three phage clones that reacted only with those IgGs. Peptides were synthesized, polymerized with glutaraldehyde, and used as antigens in ELISA assays. Each individual peptide or a mix of them was reactive with infected dogs serum. The assay was highly sensitive and specific when compared to soluble Leishmania antigen that showed cross-reactivity with anti- T. cruzi IgGs. Our results demonstrate that phage display technique is useful for selection of peptides that may represent valuable synthetic antigens for an improved serodiagnosis of CVL.